Deformation of peat soil reinforcement settlement using single-layer bamboo dendrocalamus asper - Md Yusof, Z; Khairul Anuar, N A; Abu Talib, M K; Md Dan, M F; Mohammad Noh, N (2023)
As a unique soil, peat soil has extreme characteristics such as very high compressibility when any load applies to it. It has the condition of partially decomposed plant and animal make it unsuitable used as a foundation for construction. Due to this, the reinforcement of peat must be improved or stable. The stability of peat was more stable when the reinforcement is held or tied with a strong material that can be used for the long term. Therefore, this study to identify the deformation settlement of single-layer bamboo Dendrocalamus asper that using as reinforcement for the peat. The testing at the laboratory and physical model were conducted to fulfill the objective of the study which is to identify the physical properties (water content, specific gravity, organic content, fiber content, degree of decomposition), mechanical properties (consolidation test), and displacement of settlement through physical modeling at the laboratory. The result shows that the soil collected at Kampung Parit Puteri Menangis, Benut, Johor has a moisture content of 672%, specific gravityof 1.23, organic content of 88.34 – 96.19%, fiber content of 38.1%, and categories H4 to H6 (Hemic). The compression index (Cc) was determined in the range of 0.13 to 1.54, the consolidation coefficient (Cv) was determined in the range of 0.62 to 4.925, while the coefficient of compression (Cα) was determined in the range of 0.02 to 0.048. For the displacement of the settlement of peat show the bamboo reinforcement reduce the settlement under different load. The settlement decreased by 59% of the final load 4 kg/m2 during 2 hours in the displacement 9.543 mm to 3.867 mm. It is shown that the properties of peat react with the soil and began to settle down slowly until the reading remained constant